Pregnancy induced hypertension: lipid peroxidation and antioxidant status - Shah, Aaliya; Rashid, Adila; Khan, Mosin S.; Parvez, Tabassum; Kaisar, Mir; Mudassar, Syed (International Journal of Research in Medical Sciences, 2019)
Background: Pregnancy is a stressful condition accompanied by a high energy demand and increased oxygen requirement. Oxidative stress has been recognized as a significant factor linked to hypertension. Elucidation of anti-oxidant cascade in patients with pregnancy induced hypertension (PIH). can give insights about the oxidative stress and lead to better management of the condition. It was a prospective case control study to elucidate the parameters of oxidative stress in patients with PIH. Methods: Levels of Malondialdehyde (MDA), superoxide dismutase (SOD) and catalase (CAT) were eludidated using enzyme linked immunosorbent assay (ELISA) in hypertensive mothers and their age matched pregnant and non-pregnant controls to determine the lipid peroxidation and oxidative stress. Results: A total of four hundred and twenty study subjects were enrolled in the study. Malondialdehyde levels from mothers with hypertension were significantly higher than their age matched pregnant controls. The results indicate that oxidative stress induced by pregnancy induced hypertension manifests as increased lipid peroxidation. Conclusion: There is a decrement in anti-oxidant status reflecting the ineffective scavenging of reactive oxygen species resulting in oxidative damage and tissue injury.